2019
DOI: 10.1159/000503105
|View full text |Cite
|
Sign up to set email alerts
|

Association between Use of Statin and Risk of Dementia: A Meta-Analysis of Observational Studies

Abstract: Background and Aims: The impact of statin on dementia risk reduction has been a subject of debate over the last decade, but the evidence remains inconclusive. Therefore, we performed a meta-analysis of relevant observational studies to quantify the magnitude of the association between statin therapy and the risk of dementia. Methods: We systematically searched for relevant studies published from January 2000 to March 2018 using EMBASE, Google, Google Scholar, PubMed, Scopus, and Web of Science. Two authors per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 64 publications
0
65
1
Order By: Relevance
“…Conversely, many other observational studies have found no association between PPI use and risk of dementia [437][438][439] or decreased rate of cognitive decline [452]. Metaanalyses of pooled data seem to support these results [271,272,453,454]. However, intervention trials completed to date have not supported a link between statin use and cognitive status [233,455].…”
Section: Stressmentioning
confidence: 99%
“…Conversely, many other observational studies have found no association between PPI use and risk of dementia [437][438][439] or decreased rate of cognitive decline [452]. Metaanalyses of pooled data seem to support these results [271,272,453,454]. However, intervention trials completed to date have not supported a link between statin use and cognitive status [233,455].…”
Section: Stressmentioning
confidence: 99%
“…They may reduce the incidence of dementia by regulating cholesterol metabolism in the brain [6,8]. Many previous meta-analyses [6,[9][10][11][12][13][14] suggested that the use of statins was associated with a decreased risk of dementia. A recent meta-analysis conducted by Zhang et al based on 31 studies concluded that statins reduced the risk of dementia by about 15% [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by estimates, which indicate that almost two-thirds of patients diagnosed with AD are women. A recent meta-analysis among Asians, Europeans, and Americans has shown that women are at greater risk of developing AD-associated dementia than men [35]. There is a vague explanation for this difference, but it is assumed that the greater percentage of women among AD patients is due to their longer lifespan than the opposite sex [33].…”
Section: Sex Differences In Cognition For Ad Patientsmentioning
confidence: 99%